The Dual Functions of a Bracovirus C-Type Lectin in Caterpillar Immune Response Manipulation - Wu, Xiaotong; Wu, Zhiwei; Ye, Xiqian; Pang, Lan; Sheng, Yifeng; Wang, Zehua; Zhou, Yuenan; Zhu, Jiachen; Hu, Rongmin; Zhou, Sicong; Chen, Jiani; Wang, Zhizhi; et al. (Frontiers in Immunology, 2022)
Parasitoids are widespread in natural ecosystems and normally equipped with diverse viral factors to defeat host immune responses. On the other hand, parasitoids can enhance the antibacterial abilities and improve the hypoimmunity traits of parasitized hosts that may encounter pathogenic infections. These adaptive strategies guarantee the survival of parasitoid offspring, yet their underlying mechanisms are poorly understood. Here, we focused on Cotesia vestalis, an endoparasitoid of the diamondback moth Plutella xylostella, and found that C. vestalis parasitization decreases the number of host hemocytes, leading to disruption of the encapsulation reaction. We further found that one bracovirus C-type lectin gene, CvBV_28-1, is highly expressed in the hemocytes of parasitized hosts and participates in suppressing the proliferation rate of host hemocytes, which in turn reduces their population and represses the process of encapsulation. Moreover, CvBV_28-1 presents a classical bacterial clearance ability via the agglutination response in a Ca2+-dependent manner in response to gram-positive bacteria. Our study provides insights into the innovative strategy of a parasitoid-derived viral gene that has dual functions to manipulate host immunity for a successful parasitism.